To Know the Prevalence and Risk Factors of Isolated Systolic Hypertension among Adults Aged 30 Years and Above in Davangere Taluka - Anurupa MS; Rashmi R; Shubha DB (National Journal of Community Medicine, 2019)
Background: The WHO has estimated that globally hypertension is directly responsible for about 62% of cerebrovascular disease and 49% of ischemic heart disease. The risks of stroke and coronary heart disease are directly related to both levels of systolic and dias- tolic blood pressure. Research studies has shown that Isolated sys- tolic hypertension (ISH) confers a substantial cardiovascular risk and stoke, however prevention and treatment lead to lowering of cardiovascular morbidity and mortality. Objectives:1) To know the prevalence of Isolated Systolic Hyper- tension in population aged > 30 years of Davangere Taluk.2) To identify risk factors of Isolated Systolic Hypertension. Materials and methods: It are a Community based cross sectional study conducted among persons above 30 years of Davangere taluk. Statistical analysis was performed using Percentage, proportion, chi-square and multivariate analysis. Results: A total of 2400 subjects were studied. Majority of the el- derly in our study belonged to the age group of 60-69 years (59.5%) with the mean age of 65 years (SD±5.44).It was observed that major- ity of the elderly were males (55.4%), Hindu by religion (93.3%).In the present study the overall prevalence of ISH was 25%, which was 26.4% in males and 23.6% among females. Conclusion: A significant increase in the prevalence of ISH was seen with an increase in age. Multivariate analysis showed age, high salt intake, less fruits consumption, lack of physical activity and high BMI were significant independent risk factors of ISH.